2003
DOI: 10.1177/0145482x0309700505
|View full text |Cite
|
Sign up to set email alerts
|

Haptic Exploration and Mental Estimation of Distances on a Fictitious Island: From Mind's Eye to Mind's Hand

Abstract: This study replicated Kosslyn, Ball, and Reiser's (1978) well-known experiment of a fictitious island that was specifically designed to demonstrate that visual images preserve metric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 4 publications
5
22
1
Order By: Relevance
“…Finally, our results showed that the characteristics of the language produced by the children with low vision generally either occupied an intermediate position between those observed in the language of the blind and the sighted children, or were closer to those of the latter. This result echoes much of the data obtained in the field of spatial cognition (Dekker ; Blanco & Travieso ; Heller et al . ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, our results showed that the characteristics of the language produced by the children with low vision generally either occupied an intermediate position between those observed in the language of the blind and the sighted children, or were closer to those of the latter. This result echoes much of the data obtained in the field of spatial cognition (Dekker ; Blanco & Travieso ; Heller et al . ).…”
Section: Discussionsupporting
confidence: 89%
“…Finally, our results showed that the characteristics of the language produced by the children with low vision generally either occupied an intermediate position between those observed in the language of the blind and the sighted children, or were closer to those of the latter. This result echoes much of the data obtained in the field of spatial cognition (Dekker 1993;Blanco & Travieso 2003;Heller et al 2003). Language in these children with low vision thus reflects the importance that residual vision, even when as rudimentary as blurred grey images, can have in the construction of word meaning.…”
Section: Discussionsupporting
confidence: 81%
“…First, several researchers have attributed similarities in the performance of blind and sighted individuals (i.e., convergence) to amodal spatial representations. 79 Similar performance has been found for mental rotation tasks 97-99 (but see Klatzky 73 ), mental scanning tasks, 74,95 incidental cued-recall tasks, 95 Euclidean and functional distance estimation for regular street networks, 79 and triangle completion tasks. 83 Second, some researchers have investigated the functional equivalence of spatial information acquired through different perceptual modalities (for a review, see Refs 18,130).…”
Section: Spatial Processing and Representation By Blind Peoplementioning
confidence: 64%
“…As a result, the number of studies supporting this theory may be overestimated. At the microscale, the sighted consistently outperformed the blind in a haptic version of the triangle completion task, 94 mental scanning, 95 incidental cued-recall test, 95 perspective-taking, 96 mental rotation, 97-99 distance estimation, 74 direction estimation, 100 and change detection 75 after locomotion. 101 At the mesoscale, the performance of blind participants (relative to sighted participants) is sometimes lower for inferential tasks than memory tasks.…”
Section: Persistent Modelmentioning
confidence: 97%
“…For example, through a concern with seeing with the hands (Blanco and Travieso 2003;Paterson 2006aPaterson , 2006b) and accessing museum collections through hand touch (Hetherington 2000). Research on blind touch tends to reiterate this focus on the hands.…”
Section: Assumptions About Touch: Hands and Feetmentioning
confidence: 99%